Aspiration pneumonia in a dog: Case report - Dos Santos, Emily; Souza, Mary’Anne Rodrigues de; Francielly Dultra Ribeiro, Deborah; Aparecida da Silva Bomfim, Larissa (Pubvet, 2024)
Aspiration pneumonia is a pathology resulting from the inhalation of liquid or solid contents via the airways, which leads to inflammation in the lung parenchyma. The course of the disease varies according to the amount and type of material aspirated, as well as the animal’s general state of health. The symptoms of the disease are usually acute and severe. In this sense, the drug therapy chosen for treatment depends on the degree to which the lung is compromised and the clinical signs. The surgical procedure of total or partial lobectomy can be advantageous when the lung lesions are irreversible and clinical therapy has been unsuccessful. The aim of this paper is to report the case of aspiration pneumonia in a female Labrador retriever who presented pulmonary crackles after drowning and was given a pulmonary lobectomy. Computed tomography was used to confirm the diagnosis of aspiration pneumonia. This highlights the importance of carrying out complementary tests in order to offer the animal a better therapeutic approach.